Non-targeted metabolomics and microbial analyses of the impact of oat antimicrobial peptides on rats with dextran sulfate sodium-induced enteritis - Wang, Helin; Xie, Linlin; Liu, Shufan; Dai, Anna; Chi, Xiaoxing; Zhang, Dongjie (Frontiers in Nutrition, 2023)
This study investigated the preventive and ameliorating effects of oat antimicrobial peptides (AMPs) on enteritis. In this study, oat AMPs were obtained from oat protein through enzymatic hydrolysis with alkaline protease, followed by separation and purification using 108 L cation resin. A total 48 of specific pathogen-free female Sprague-Dawley rats (200–220 g) were randomly divided into blank group, negative control group, positive control group, and experimental group (low dose, medium dose, high dose) according to body weight. In order to study the preventive effect of antimicrobial peptides on enteritis, the experimental group was also given DSS and antimicrobial peptides at the same time. After 7 days of feeding, fasting for 12h,dissected rats. Next, take colon samples for haemotoxylin and eosin (H&E) stain, antioxidant activities of SOD, MDA, GSH-PX, MPO were determined and were performed to identify the metabolites.The intestinal microbial diversity was measured in rat feces based on lllumina Novaseq sequencing platform and Paired-End sequencing. The BMKCloud biological platform was also used to conduct joint analysis of non-targeted metabolites and microorganisms. H&E staining showed a large number of inflammatory cells, as well as the expansion of the gland in the negative control group, while there were few inflammatory cells in the medium- and high-dose groups without large-scale inflammatory tissue changes and cystic gland expansion. There was a significant difference in antioxidant capacity between the high dose group and the negative control group. The results indicated that oat AMPs had preventive and anti-enteritis effects and improved the antioxidant capacity of the colonic mucosa. Oat AMPs improved the microbial structure in the gut; it increased the abundance of probiotics, such as Romboutsia and Ruminococcus, and reduced the abundance of Bacteroides-eggerthii-DSM-20697 and Desulfovibrionaceae. The results of combined metabolomic and microbiome analysis showed that oat AMPs converted amino acids into phospholipids in vivo through protein digestion and absorption-related metabolic pathways in the intestinal tract to promote phospholipid production, repair damaged cell membrane. These results indicated that oat AMPs had significant anti-inflammatory effect and alleviated intestinal inflammation through protein digestion and absorption-related metabolic pathways, thereby inhibiting further development of enteritis to colon cancer.